THE EFFECT OF CORPORATE RISK IN MEDIATING THE RELATIONSHIP OF SUSTAINABLE FINANCE ON CORPORATE PERFORMANCE - Rampisela, Dominggus Richardo (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2023)
The purpose of this study is to analyze the impact of Sustainable Finance mediated by Company Risk on Company Performance for the period 2015 to 2019. Sustainable Finance is calculated using the SFD value (total value of sustainability disclosures) with POJK 51. Corporate risk is calculated using the NPL ratio. Company performance is calculated using the EVA ratio. Meanwhile, Bank Size is calculated using the total asset logarithm. The population in this study are banking companies listed on the Indonesia Stock Exchange during the 2015-2019 period. The research sample was taken using the saturated sample technique. The data used in this study is secondary data, namely in the form of company financial statements that have been audited and obtained through access to www.idx.co.id. This research method uses the PLS research method. The results of the study show that Sustainable Finance has a significant negative effect on Company Risk and Corporate Risk has a negative impact on Company Performance. Also, Sustainable Finance mediated by Company Risk has a significant positive effect on the Company's Performance.